Corrosion detection using labVIEW for robotic inspection of boiler headers - Zulkifli N.A.; Sahari K.S.M.; Anuar A.; Aziz M.A. (Springer Verlag, 2023)
Boiler header is the backbone of piping system inside thermal power plant which is used to tie multiple steam mains to one boiler. It is important to check the header for any signs of defects. This paper presents an image based approach to detect cracks and corrosions inside a boiler header using LabVIEW software. After an image of the boiler header inner wall is captured, thresholding technique is applied to manage background variation of the acquired image. Then, the boundaries of the corroded area are identified by using edge detection algorithm. The last step is to apply particle analysis for parameters measurement. Experiments are carried out on a 360° view of a cross-section of a boiler header for inspecting the surface defects of the boiler headers. The result from the experiment shows a reasonable success rate of correctly identifying corrosion inside the header. © 2014 Springer Science+Business Media Singapore.